2016
DOI: 10.1167/iovs.15-17557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Penetrating Keratoplasty and Keratoprosthesis Implantation on the Posterior Segment of the Eye

Abstract: PurposeTo compare the effects of post-penetrating keratoplasty (PK) and post-keratoprosthesis (KPro) surgery-related inflammation on the posterior segment of the eye and to assess inhibition of tumor necrosis factor alpha (TNFα) and interleukin-1 beta (IL-1β) on these effects.MethodsBALB/C (syngeneic) or C57BL/6 (allogeneic) corneas were transplanted onto BALB/C host beds as part of PK or miniature KPro (m-KPro) implantation. Intraocular pressure (IOP) was measured via an intracameral pressure sensor; tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…12 Prompt inhibition with an anti-TNF-α antibody (infliximab) after alkali burn has been shown to protect the cornea and promote healing. 12,13 This effect has also been demonstrated in animals with experimental keratoprosthesis 14 and in other settings. 15,16 Clinically, infliximab has been found to very effectively suppress inflammation after keratoprosthesis surgery in autoimmune diseases, 17,18 as well as in corneal ulceration.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…12 Prompt inhibition with an anti-TNF-α antibody (infliximab) after alkali burn has been shown to protect the cornea and promote healing. 12,13 This effect has also been demonstrated in animals with experimental keratoprosthesis 14 and in other settings. 15,16 Clinically, infliximab has been found to very effectively suppress inflammation after keratoprosthesis surgery in autoimmune diseases, 17,18 as well as in corneal ulceration.…”
mentioning
confidence: 70%
“…14 Sections from burned and contralateral nonburned eyes were used for comparison. A portion of the nerve between the orbit and chiasm was surgically dissected, and fixed with half strength Karnovsky's fixative (2% formaldehyde + 2.5% glutaraldehyde, in 0.1 M sodium cacodylate buffer, pH 7.4 [Electron Microscopy Sciences, Hatfield, PA, USA]) for a minimum of 24 hours at 40°C.…”
Section: Methodsmentioning
confidence: 99%
“…1 One form of this transplantation, penetrating keratoplasty (PK), is a sight-saving surgery in many patients with corneal blindness. 2 Overall, approximately 90% of all corneal transplantation procedures performed in 95 reporting countries are PK, regardless of the surgical indication. 3,4 Patients who undergo PK may experience eyelid ptosis [5][6][7] and blepharoptosis that may restrict the visual acuity and the visual field that was improved with the PK.…”
Section: Introductionmentioning
confidence: 99%
“…Corneal transplantation is the most common type of tissue transplantation performed worldwide [ 1 ]. One form of this transplantation, penetrating keratoplasty (PK), is a sight-saving surgery in many patients with corneal blindness [ 2 ]. Overall, approximately 90% of all corneal transplantation procedures performed in 95 reporting countries are PK, regardless of the surgical indication [ 3 , 4 ].…”
mentioning
confidence: 99%
“…Increased expression of proinflammatory cytokines tumor necrosis factor (TNF)-α and interleukin (IL)-1β have been shown in a miniature KPro murine model. 15,19 Our team also showed that soluble TNF-α is a major culprit in RGC death in glaucoma and that TNF-α inhibition is beneficial. 20 However, neither the exact mechanism of KPro glaucoma nor the role of cytokines has been elucidated yet in humans.…”
mentioning
confidence: 96%